How does biochar reduce N2O emission from soil? - a review of mechanisms - Xiao Wang; Camille Nunes Leite; Bo Thamdrup; Sander Bruun; Hans Chr. Bruun Hansen (Soil Biology and Biochemistry, 2026)

Kinetics of sulfate‐ and iron‐dependent anaerobic methane oxidation in freshwater lake sediment - Alina Mostovaya; Michael Wind‐Hansen; Bo Thamdrup (Limnology and Oceanography, 2026)
Anaerobic oxidation of methane (AOM) is a potentially important sink for methane in freshwater sediments. Assessing the contribution of AOM to methane budgets requires an understanding of AOM process kinetics, yet such information remains scarce. In the present study, we experimentally quantified the kinetics of AOM in the sediments of the Danish Lake Ørn, where sulfate‐ and iron‐dependent AOM occur side by side. The process exhibited saturation kinetics for methane, sulfate, and Fe(III), and the derived half‐saturation constants ( K m ) implied that these substrates co‐limit in situ AOM rates across concentration ranges typical for the study site and many other freshwater systems. Nevertheless, values of K m for methane (414 ± 79 μ M) and sulfate (31 ± 29 μ M) were low relative to marine systems, indicating an adaptation of the microbial community to the limnic environment. Experiments involving a synthetic analog of humic substances, anthraquinone‐2,6‐disulfonate (AQDS), demonstrated that sedimentary organic matter could play a role in alleviating restrictive Fe‐AOM kinetics. Incorporation of the obtained kinetic parameters into predictions of AOM rate profiles based on methane, sulfate, and Fe(III) concentrations revealed similar contributions of sulfate‐ and Fe(III)‐AOM pathways in the sulfate–methane transition zone. Our study expands the limited knowledge on the kinetics of microbial methane oxidation in freshwater systems and highlights the potential importance of AOM in regulating methane emissions from inland waters.

Nitrification in the oxygen-deficient uppermost mesopelagic layer of a marginal basin in the southeastern Gulf of California - Cristian Hakspiel-Segura; Aída Martínez-López; Bo Thamdrup; Gerardo Verdugo-Díaz; Diana Escobedo-Urías (Regional Studies in Marine Science, 2025)

Uniform selective pressures within redox zones drive gradual changes in microbial community composition in hadal sediments - Clemens Schauberger; David Seki; Elise M. Cutts; Ronnie N. Glud; Bo Thamdrup (Environmental Microbiology, 2023)
Microbial communities in marine sediments are highly diverse, yet the processes that give rise to this complexity are unclear. It has been proposed that benthic microbial communities must be continuously re‐seeded from the water column because dispersal within the sediment is severely limited. Previous studies consistently report that the composition of the microbial community gradually changes with sediment depth. However, the relative contributions of the processes that underlie these compositional gradients have not been determined, and it is unknown whether microbial dispersal is indeed too slow to outpace burial. Here, we applied ecological statistical frameworks to 16S rRNA gene amplicon‐based community composition data from Atacama Trench sediments to investigate the links between biogeochemistry, burial, and microbial community assembly processes. We confirm that dispersal limitation affects microbial communities and find that gradual changes in community composition are driven by selective pressures that change abruptly across the discrete boundaries between redox zones rather than along continuous biogeochemical gradients, while selective pressures are uniform within each zone. The gradual changes in community composition over centimetres of depth within a zone hence reflects a decades‐long response to the abruptly changing selective pressures.

Aerobic and anaerobic methane oxidation in a seasonally anoxic basin - Herdís G. R. Steinsdóttir; Clemens Schauberger; Snehit Mhatre; Bo Thamdrup; Laura A. Bristow (Limnology and Oceanography, 2022)
Shallow coastal waters are dynamic environments that dominate global marine methane emissions. Particularly high methane concentrations are found in seasonally anoxic waters, which are spreading in eutrophic coastal systems, potentially leading to increased methane emissions to the atmosphere. Here we explore how the seasonal development of anoxia influenced methane concentrations, rates of methane oxidation, and the community composition of methanotrophs in the shallow eutrophic water column of Mariager Fjord, Denmark. Our results show the development of steep concentration gradients toward the oxic–anoxic interface as methane accumulated to 1.4 μ M in anoxic bottom waters. Yet, the fjord possessed an efficient microbial methane filter near the oxic–anoxic interface that responded to the increasing methane flux. In experimental incubations, methane oxidation near the oxic–anoxic interface proceeded both aerobically and anaerobically with nearly equal efficiency reaching turnover rates as high as 0.6 and 0.8 d −1 , respectively, and was seemingly mediated by members of the Methylococcales belonging to the Deep Sea‐1 clade. Throughout the period, both aerobic and anaerobic methane oxidation rates were high enough to consume the estimated methane flux. Thus, our results indicate that seasonal anoxia did not increase methane emissions.

Anaerobic methane oxidation in a coastal oxygen minimum zone: spatial and temporal dynamics - Herdís G. R. Steinsdóttir; Eddy Gómez‐Ramírez; Snehit Mhatre; Clemens Schauberger; Anthony D. Bertagnolli; Zoe A. Pratte; Frank J. Stewart; Bo Thamdrup; Laura A. Bristow (Environmental Microbiology, 2022)
Summary Coastal waters are a major source of marine methane to the atmosphere. Particularly high concentrations of this potent greenhouse gas are found in anoxic waters, but it remains unclear if and to what extent anaerobic methanotrophs mitigate the methane flux. Here we investigate the long‐term dynamics in methanotrophic activity and the methanotroph community in the coastal oxygen minimum zone (OMZ) of Golfo Dulce, Costa Rica, combining biogeochemical analyses, experimental incubations and 16S rRNA gene sequencing over 3 consecutive years. Our results demonstrate a stable redox zonation across the years with high concentrations of methane (up to 1.7 μmol L −1 ) in anoxic bottom waters. However, we also measured high activities of anaerobic methane oxidation in the OMZ core (rate constant, k , averaging 30 yr −1 in 2018 and 8 yr −1 in 2019–2020). The OPU3 and Deep Sea‐1 clades of the Methylococcales were implicated as conveyors of the activity, peaking in relative abundance 5–25 m below the oxic–anoxic interface and in the deep anoxic water respectively. Although their genetic capacity for anaerobic methane oxidation remains unexplored, their sustained high relative abundance indicates an adaptation of these clades to the anoxic, methane‐rich OMZ environment, allowing them to play major roles in mitigating methane fluxes.

Sulfate‐ and iron‐dependent anaerobic methane oxidation occurring side‐by‐side in freshwater lake sediment - Alina Mostovaya; Michael Wind‐Hansen; Paul Rousteau; Laura A. Bristow; Bo Thamdrup (Limnology and Oceanography, 2022)
Anaerobic oxidation of methane (AOM) is a potentially important methane sink in lake sediments, but the biogeochemistry and microbial ecology of this process are understudied. Potential electron acceptors for AOM include Fe(III) and sulfate; however, it is not clear to which extent low sulfate concentrations constrain the coupling of AOM to sulfate reduction, nor if Fe(III) reduction drives AOM directly or via a cryptic sulfur cycle. We investigated AOM pathways in the sediment of iron‐rich Danish Lake Ørn through anoxic sediment slurry incubations with additions of 13 C‐labeled methane as a substrate, sulfate and Fe(III) as potential electron acceptors, and molybdate as an inhibitor of sulfate reduction. The experiments demonstrated the co‐occurrence of sulfate‐ and iron‐dependent modes of AOM, with the former supported by recycling of sulfate coupled to iron reduction. Quantitative PCR analysis demonstrated the abundance of archaea of the ANME‐2d clade ( Ca . Methanoperedenaceae) as likely drivers of AOM. Our study demonstrates that sulfate‐dependent AOM can consume methane at sulfate concentrations typical for freshwater systems and emphasizes the importance of sulfur and iron cycling in the regulation of methane emission from freshwater sediments.

Sulfur cycling in oceanic oxygen minimum zones - Cameron M. Callbeck; Donald E. Canfield; Marcel M. M. Kuypers; Pelin Yilmaz; Gaute Lavik; Bo Thamdrup; Carsten J. Schubert; Laura A. Bristow (Limnology and Oceanography, 2021)
The sulfur cycle is an important, although understudied facet of today's modern oxygen minimum zones (OMZs). Sulfur cycling is most active in highly productive coastal OMZs where sulfide‐rich sediments interact with the overlying water column, forming a tightly coupled benthic‐pelagic sulfur cycle. In such productive coastal systems, highly eutrophic and anoxic conditions can result in the benthic release of sulfide leading to an intensification of OMZ‐shelf biogeochemistry. Active blooms involving a succession of sulfide‐oxidizing bacteria detoxify sulfide and reduce nitrate to N 2 , while generating nitrite and ammonium that augment anammox and nitrification. Furthermore, the abiotic interactions of sulfide with trace metals may have the potential to moderate nitrous oxide emissions. While sulfide/sulfur accumulation events were previously considered to be rare, new evidence indicates that events can develop in OMZ shelf waters over prolonged periods of anoxia. The prevalence of these events has ramifications for nitrogen loss and greenhouse gas emissions, including other linked cycles involving carbon and phosphorous. Sulfur‐based metabolisms and activity also extend into the offshore OMZ as a result of particle microniches and lateral transport processes. Moreover, OMZ waters ubiquitously host a community of organosulfur‐based heterotrophs that ostensibly moderate the turnover of organic sulfur, offering an exciting avenue for future research. Our synthesis highlights the widespread distribution and multifaceted nature of the sulfur cycle in oceanic OMZs.

Spatial variability of prokaryotic and viral abundances in the Kermadec and Atacama Trench regions - Clemens Schauberger; Mathias Middelboe; Morten Larsen; Logan M. Peoples; Douglas H. Bartlett; Finn Kirpekar; Ashley A. Rowden; Frank Wenzhöfer; Bo Thamdrup; Ronnie N. Glud (Limnology and Oceanography, 2021)
Hadal trenches represent the deepest part of the ocean and are dynamic depocenters with intensified prokaryotic activity. Here, we explored the distribution and drivers of prokaryotic and viral abundance from the ocean surface and 40 cm into sediments in two hadal trench regions with contrasting surface productivity. In the water column, prokaryotic and viral abundance decreased with water depth before reaching a rather stable level at ~ 4000 m depth at both trench systems, while virus to prokaryote ratios were increasing with depth, presumably reflecting the declining availability of organic material. Prokaryotic and viral abundances in sediments were lower at the adjacent abyssal sites than at the hadal sites and declined exponentially with sediment depth, closely tracking the attenuation of total organic carbon (TOC) content. In contrast, hadal sediment exhibited erratic depth profiles of prokaryotes and viruses with many subsurface peaks. The prokaryotic abundance correlated well to extensive fluctuations in TOC content at centimeter scale, which were likely caused by recurring mass wasting events. Yet while prokaryotic and viral abundances cross correlated well in the abyssal sediments, there was no clear correlation in the hadal sites. The results suggested that dynamic depositional conditions and higher substrate availability result in a high spatial heterogeneity in viral and prokaryotic abundances in hadal sediments in comparison to more stable abyssal settings. We argue that these conditions enhance the relatively importance of viruses for prokaryotic mortality and carbon recycling in hadal settings.

Influence of settling organic matter quantity and quality on benthic nitrogen cycling - Séréna Albert; Stefano Bonaglia; Nellie Stjärnkvist; Monika Winder; Bo Thamdrup; Francisco J. A. Nascimento (Limnology and Oceanography, 2021)
Coastal sediments are major contributors to global carbon (C) mineralization and nutrient cycling and are tightly linked to processes in the pelagic environment. In this study, we aimed to investigate the regulating potential of quantity and quality of planktonic organic matter (OM) deposition on benthic metabolism, with a particular focus on nitrogen (N) cycling processes. We simulated inputs of spring (C : N 10.9) and summer (C : N 5.6) plankton communities in high and low quantities to sediment cores, and followed oxygen consumption, nutrient fluxes as well as nitrate reduction rates, that is, denitrification and dissimilatory nitrate reduction to ammonium for 10 d. Our results demonstrate the primary importance of OM quality in determining the fate of organic N once it settles to the sediment surface. Settling of N‐rich summer plankton material resulted in a ∼ twofold lower denitrification efficiency (40–56%) compared to N‐poor spring plankton (88–115%). This indicates that N‐rich plankton deposition favors recycling of inorganic nutrients to the water column over N‐loss via denitrification. OM quantity was positively related to mineralization activity, but this neither directly affected N fluxes nor denitrification activity, highlighting the complex interplay between the OM quantity and quality in regulating N cycling. In light of these new findings, we support the use of simple qualitative indicators such as C : N ratio of OM to investigate how future changes in benthic‐pelagic coupling might influence N budgets at the sediment–water interface.

Anaerobic methane oxidation is an important sink for methane in the ocean's largest oxygen minimum zone - Bo Thamdrup; Herdís G. R. Steinsdóttir; Anthony D. Bertagnolli; Cory C. Padilla; Nastassia V. Patin; Emilio Garcia‐Robledo; Laura A. Bristow; Frank J. Stewart (Limnology and Oceanography, 2019)
We investigated methane oxidation in the oxygen minimum zone (OMZ) of the eastern tropical North Pacific (ETNP) off central Mexico. Methane concentrations in the anoxic core of the OMZ reached ~ 20 nmol L −1 at off shelf sites and 34 nmol L −1 at a shelf site. Rates of methane oxidation were determined in ship‐board incubations with 3 H‐labeled methane at O 2 concentrations 0–75 nmol L −1 . In vertical profiles at off‐shelf stations, highest rates were found between the secondary nitrite maximum at ~ 130 m and the methane maximum at 300–400 m in the anoxic core. Methane oxidation was inhibited by addition of 1 μ mol L −1 oxygen, which, together with the depth distribution, indicated an anaerobic pathway. A coupling to nitrite reduction was further indicated by the inhibitory effect of the nitric oxide scavenger 2‐phenyl‐4,4,5,5‐tetramethylimidazoline‐1‐oxyl‐3‐oxide (PTIO). Metatranscriptomes from the anoxic OMZ core supported the likely involvement of nitrite‐reducing bacteria of the NC10 clade in anaerobic methane oxidation, but also indicated a potential role for nitrate‐reducing euryarchaeotal methane oxidizers (ANME‐2d). Gammaproteobacteria of the Methanococcales were further detected in both 16S rRNA gene amplicons and metatranscriptomes, but the role of these presumed obligately aerobic methane oxidizers in the anoxic OMZ core is unclear. Given available estimates of water residence time, the measured rates and rate constants (up to ~ 1 yr −1 ) imply that anaerobic methane oxidation is a substantial methane sink in the ETNP OMZ and hence attenuates the emission of methane from this and possibly other OMZs.

Denitrification, anaerobic ammonium oxidation, and dissimilatory nitrate reduction to ammonium in an East African Great Lake (Lake Kivu) - Fleur A. E. Roland; François Darchambeau; Alberto V. Borges; Cédric Morana; Loreto De Brabandere; Bo Thamdrup; Sean A. Crowe (Limnology and Oceanography, 2018)
We investigated anaerobic nitrogen (N) cycling in the water column of Lake Kivu, a deep meromictic tropical lake in East Africa. Data were collected at one station in the Northern Basin and one in the Southern Basin, during two sampling campaigns (June 2011—dry season, and February 2012—rainy season). Short‐term incubations of sulfide‐free water with 15 N‐labeled substrates revealed high potential denitrification and dissimilatory nitrate reduction to ammonium (DNRA) rates (up to 350 and 36 nmol N produced L −1 h −1 , respectively), while anaerobic ammonium oxidation (anammox) was lower (up to 3.3 nmol N produced L −1 h −1 ). However, anammox rates were 15 nmol N produced L −1 h −1 when 15 was added at depths where concentrations were very low ( −1 ). With the addition of 5 μmol L −1 of 15 and 10 μmol L −1 of H 2 S, denitrification and anammox were stimulated in the Northern Basin, while the increase of DNRA rates was less notable. In the Southern Basin, the addition of H 2 S decreased denitrification rates, probably because of competition with DNRA, which increased, while no effect was observed on anammox. This study puts into evidence the co‐occurrence of denitrification, anammox and DNRA, for the first time in a great tropical lake, and underlines the spatial heterogeneity of these processes. Contrary to numerous reports in literature, we show that anammox can significantly occur in presence of H 2 S, suggesting that the contribution of anammox in the N cycle may be underestimated.

N 2 production through denitrification and anammox across the continental margin (shelf–slope–rise) of the Ulleung Basin, East Sea - Taehee Na; Bo Thamdrup; Bomina Kim; Sung‐Han Kim; Verona Vandieken; Dong‐Jin Kang; Jung‐Ho Hyun (Limnology and Oceanography, 2018)
Experimental determinations of nitrogen cycling in deep‐sea sediments are strongly underrepresented in the databases. To investigate the total N 2 production rates and relative contribution of denitrification and anaerobic ammonium oxidation (anammox) to benthic fixed‐N removal processes, we conducted 15 N isotope‐labeling incubation experiments in whole cores and slurries at nine stations across the continental margin from the shelf ( 2000 m) Ulleung Basin (UB) in the East Sea. The total N 2 production rates (anammox plus denitrification) in the center of the UB (8.4 ± 0.2 μmol N m −2 h −1 ) were high compared to most other deep‐sea sediments at similar water depths. Denitrification rates decreased from the shelf (7.6 ± 0.6 μmol N m −2 h −1 ) to the basin (3.2 ± 0.4 μmol N m −2 h −1 ), in proportion to benthic oxygen consumption, whereas anammox rates remained relatively constant or even increased slightly (1.3–4.1 μmol N m −2 h −1 ). The contribution of anammox to the total N 2 production ( ra ) increased with increasing water depth from the shelf (ca. 17%) to the basin (ca. 56%). The enhanced ra in the center of the UB was associated with an increased availability of nitrite for anammox, which was likely a result of the competitive suppression of denitrification by manganese reduction under MnO 2 ‐rich conditions. Our results emphasize the importance of anammox as a sink for reactive nitrogen in deep‐sea sediments and contribute toward a mechanistic understanding of the factors controlling benthic reactive nitrogen loss in the ocean.

Effect of settled diatom‐aggregates on benthic nitrogen cycling - Ugo Marzocchi; Bo Thamdrup; Peter Stief; Ronnie N. Glud (Limnology and Oceanography, 2018)
The marine sediment hosts a mosaic of microhabitats. Recently it has been demonstrated that the settlement of phycodetrital aggregates can induce local changes in the benthic O 2 distribution due to confined enrichment of organic material and alteration of the diffusional transport. Here, we show how this microscale O 2 shift substantially affects benthic nitrogen cycling. In sediment incubations, the settlement of diatom‐aggregates markedly enhanced benthic O 2 and consumption and stimulated and production. Oxygen microprofiles revealed the rapid development of anoxic niches within and underneath the aggregates. During 120 h following the settling of the aggregates, denitrification of from the overlying water increased from 13.5 μmol m −2 h −1 to 24.3 μmol m −2 h −1 , as quantified by 15 N enrichment experiment. Simultaneously, N 2 production from coupled nitrification‐denitrification decreased from 33.4 μmol m −2 h −1 to 25.9 μmol m −2 h −1 , probably due to temporary inhibition of the benthic nitrifying community. The two effects were of similar magnitude and left the total N 2 production almost unaltered. At the aggregate surface, nitrification was, conversely, very efficient in oxidizing liberated by mineralization of the aggregates. The produced was preferentially released into the overlying water and only a minor fraction contributed to denitrification activity. Overall, our data indicate that the abrupt change in O 2 microdistribution caused by aggregates stimulates denitrification of from the overlying water, and loosens the coupling between benthic nitrification and denitrification both in time and space. The study contributes to expanding the conceptual and quantitative understanding of how nitrogen cycling is regulated in dynamic benthic environments.

Metabolic potential and in situ activity of marine Marinimicrobia bacteria in an anoxic water column - Anthony D. Bertagnolli; Cory C. Padilla; Jennifer B. Glass; Bo Thamdrup; Frank J. Stewart (Environmental Microbiology, 2017)
Summary Marinimicrobia bacteria are widespread in subeuphotic areas of the oceans and particularly abundant in oxygen minimum zones (OMZs). Information on Marinimicrobia metabolism is sparse, making the biogeochemical influence of this group challenging to predict. Here, metagenome‐assembled genomes representing Marinimicrobia subgroups PN262000N21 and ARCTIC96B‐7 were retrieved to near completion (97% and 94%) from OMZ metagenomes, with contamination (14.1%) observed only in ARCTIC96B‐7. Genes for aerobic carbon monoxide (CO) oxidation, polysulfide metabolism and hydrogen utilization were identified only in PN262000N21, while genes for partial denitrification occurred in both genomes. Transcripts mapping to these genomes increased from

Nutrient availability limits biological production in Arctic sea ice melt ponds - Heidi Louise Sørensen; Bo Thamdrup; Erik Jeppesen; Søren Rysgaard; Ronnie Nøhr Glud (Polar Biology, 2017)

Fixed-Nitrogen Loss Associated with Sinking Zooplankton Carcasses in a Coastal Oxygen Minimum Zone (Golfo Dulce, Costa Rica) - Peter Stief; Ann Sofie B. Lundgaard; Álvaro Morales-Ramírez; Bo Thamdrup; Ronnie N. Glud (Frontiers in Marine Science, 2017)

Metagenomic Binning Recovers a Transcriptionally Active Gammaproteobacterium Linking Methanotrophy to Partial Denitrification in an Anoxic Oxygen Minimum Zone - Cory C. Padilla; Anthony D. Bertagnolli; Laura A. Bristow; Neha Sarode; Jennifer B. Glass; Bo Thamdrup; Frank J. Stewart (Frontiers in Marine Science, 2017)

Copepod carcasses as microbial hot spots for pelagic denitrification - Ronnie N. Glud; Hans‐Peter Grossart; Morten Larsen; Kam W. Tang; Kristine E. Arendt; Søren Rysgaard; Bo Thamdrup; Torkel Gissel Nielsen (Limnology and Oceanography, 2015)
Copepods are exposed to a high non‐predatory mortality and their decomposing carcasses act as microniches with intensified microbial activity. Sinking carcasses could thereby represent anoxic microenvironment sustaining anaerobic microbial pathways in otherwise oxic water columns. Using non‐invasive O 2 imaging, we document that carcasses of Calanus finmarchicus had an anoxic interior even at fully air‐saturated ambient O 2 level. The extent of anoxia gradually expanded with decreasing ambient O 2 levels. Concurrent microbial sampling showed the expression of nitrite reductase genes ( nirS ) in all investigated carcass samples and thereby documented the potential for microbial denitrification in carcasses. The nirS gene was occasionally expressed in live copepods, but not as consistently as in carcasses. Incubations of sinking carcasses in 15 amended seawater demonstrated denitrification, of which on average 34% ± 17% ( n = 28) was sustained by nitrification. However, the activity was highly variable and was strongly dependent on the ambient O 2 levels. While denitrification was present even at air‐saturation (302 μ mol L −1 ), the average carcass specific activity increased several orders of magnitude to ∼ 1 nmol d −1 at 20% air‐saturation (55 μ mol O 2 L −1 ) at an ambient temperature of 7°C. Sinking carcasses of C. finmarchicus therefore represent hotspots of pelagic denitrification, but the quantitative importance as a sink for bioavailable nitrogen is strongly dependent on the ambient O 2 level. The importance of carcass associated denitrification could be highly significant in O 2 depleted environments such as Oxygen Minimum Zones (OMZ).

Biogeochemical and metagenomic analysis of nitrite accumulation in the G ulf of M exico hypoxic zone - Laura A. Bristow; Neha Sarode; John Cartee; Alejandro Caro‐Quintero; Bo Thamdrup; Frank J. Stewart (Limnology and Oceanography, 2015)
The Louisiana Shelf in the Gulf of Mexico experiences recurrent bottom water hypoxia under summertime eutrophic conditions. The onset, maintenance, and breakdown of hypoxia are associated with dynamic microbial biogeochemical cycles. However, the distribution of microbial taxa and metabolisms across Shelf oxygen gradients remains under‐characterized. We combined biogeochemical analyses of nitrogen (N) distributions and metabolic rates with metagenomic and metatranscriptomic analysis of summertime Shelf waters. Samples from an east–west transect during July 2012 revealed an inverse relationship between nitrite and oxygen concentrations, with concentrations exceeding 1 μmol L −1 at ∼ 50% oxygen saturation and reaching 4.6 μmol L −1 at the most oxygen‐depleted sites. Historical data confirms that nitrite accumulation occurs frequently in this region both above and below the hypoxic threshold. Experimental incubations demonstrated a strong decoupling between the two steps of nitrification, with ammonia oxidation proceeding up to 30 times faster than nitrite oxidation under low oxygen. 16S rRNA gene, metagenome, and metatranscriptome sequencing revealed a diverse microbial community, stratified over shallow (

Temporal dynamics of nitrogen loss in the coastal upwelling ecosystem off central Chile: Evidence of autotrophic denitrification through sulfide oxidation - Alexander Galán; Juan Faúndez; Bo Thamdrup; Juan Francisco Santibáñez; Laura Farías (Limnology and Oceanography, 2014)
Coastal upwelling areas are highly productive marine systems in which the development of oxygen‐depleted conditions and the availability of diverse electron donors (e.g., organic matter, , H 2 S) favor the processes involved in nitrogen (N) loss. We characterize the temporal and vertical variability of anammox and denitrification over the continental shelf off central Chile (36.5°S), through 15 N and 13 C tracer experiments, including amendments with H 2 S and along with measurements of 15 N 2 and 15 N 2 O production and oceanographic variables during a year (2009 to 2010). Restricted to the bottom waters, both anammox and denitrification contributed similarly (∼ 500 nmol N 2 L −1 d −1 ) to N loss during spring, while a marked decrease in the activity of these processes occurred in summer (103 and 14 nmol N 2 L −1 d −1 for anammox and denitrification, respectively). During fall, denitrification was the only contributor to the observed nitrogen deficit (894 nmol N 2 L −1 d −1 ). Interestingly, a substantial increase in the rates of denitrification (∼ 1200 nmol N 2 L −1 d −1 ) and dark 13 C assimilation were observed after the addition of H 2 S, indicating an autotrophic contribution to denitrification, which could be fueled in situ by H 2 S emitted from sediments or produced in the water column. The observed patterns seem to be controlled (stimulated or inhibited) by the availability of oxygen, organic matter, and H 2 S. This study establishes the magnitude and co‐occurrence of the different processes responsible for N removal in the coastal upwelling system of central Chile. This linkage of the nitrogen, carbon, and sulfur cycles is relevant to a global climate change scenario.

Vertical partitioning of nitrogen‐loss processes across the oxic‐anoxic interface of an oceanic oxygen minimum zone - Loreto De Brabandere; Don E. Canfield; Tage Dalsgaard; Gernot E. Friederich; Niels Peter Revsbech; Osvaldo Ulloa; Bo Thamdrup (Environmental Microbiology, 2014)
Summary We investigated anammox, denitrification and dissimilatory reduction of nitrite to ammonium ( DNRA ) activity in the E astern T ropical S outh P acific oxygen minimum zone ( OMZ ) off northern C hile, at high‐depth resolution through the oxycline into the anoxic OMZ core. This was accompanied by high‐resolution nutrient and oxygen profiles to link changes in nitrogen transformation rates to physicochemical characteristics of the water column. Denitrification was detected at most depths, but anammox was the most active N 2 ‐producing process, while DNRA was not detectable. Anammox and denitrification were mainly active in the anoxic OMZ core while activity was low to not detectable in the oxycline, except in association with an intrusion of OMZ core water. This indicates that continuous exposure to even submicromolar oxygen levels inhibits the processes either directly or through nitrite limitation. Anammox activity did not peak at the oxic‐anoxic boundary but 20–50 m below matching the salinity maximum of the E quatorial S ubsurface W ater. This suggests that water history plays a major role for anammox activity possibly due to slow growth of anammox bacteria. Denitrification peaked deeper than anammox, likely reflecting a shift in the balance between this process and nitrate reduction to nitrite, governed by the relative availability of nitrate and nitrite.

Competition for inorganic carbon between oxygenic and anoxygenic phototrophs in a hypersaline microbial mat, G uerrero N egro, M exico - Niko Finke; Tori M. Hoehler; Lubos Polerecky; Benjamin Buehring; Bo Thamdrup (Environmental Microbiology, 2013)
Summary While most oxygenic phototrophs harvest light only in the visible range (400–700 nm, VIS ), anoxygenic phototrophs can harvest near infrared light (> 700 nm, NIR ). To study interactions between the photosynthetic guilds we used microsensors to measure oxygen and gross oxygenic photosynthesis ( gOP ) in a hypersaline microbial mat under full ( VIS + NIR ) and VIS illumination. Under normal dissolved inorganic carbon ( DIC ) concentrations (2 mM ), volumetric rates of gOP were reduced up to 65% and areal rates by 16–31% at full compared with VIS illumination. This effect was enhanced (reduction up to 100% in volumetric, 50% in areal rates of gOP ) when DIC was lowered to 1 mM , but diminished at 10 mM DIC or lowered pH . In conclusion, under full‐light illumination anoxygenic phototrophs are able to reduce the activity of oxygenic phototrophs by efficiently competing for inorganic carbon within the highly oxygenated layer. Anoxygenic photosynthesis, calculated from the difference in gOP under full and VIS illumination, represented between 10% and 40% of the C ‐fixation. The DIC depletion in the euphotic zone as well as the significant C ‐fixation by anoxygenic phototrophs in the oxic layer influences the carbon isotopic composition of the mat, which needs to be taken into account when interpreting isotopic biosignals in geological records.

Anaerobic oxidation of methane in an iron‐rich Danish freshwater lake sediment - Katrin à. Norði; Bo Thamdrup; Carsten J. Schubert (Limnology and Oceanography, 2013)
Freshwater systems are identified as one of the main natural methane sources, but little is known about the importance of anaerobic oxidation of methane (AOM) in these systems. We investigated AOM in a lake sediment characterized by a high reactive iron content, normal sulfate concentrations in the bottom water (∼ 250 µmol L −1 ), and a relatively deep sulfate penetration of ∼ 14 cm, which facilitated the spatial resolution of the zones of methane production and consumption. Methane concentrations, δ 13 C methane profiles, and directly measured and modeled AOM rates all consistently demonstrated methane consumption throughout the anoxic, nitrate‐free, Fe(III)‐ and sulfate‐containing zone, oxidizing ∼ 90% of the diffusive methane flux. Thus, the concentration gradient of methane was steepest at the base of the Fe(III) and sulfate zone and decreased strongly toward the sediment surface; while δ 13 CH 4 increased from −1 , which suggests a possible coupling of AOM to the reduction of more crystalline Fe(III) oxides. Alternatively, AOM could be coupled to sulfate reduction, which was in turn supported by a cryptic sulfur cycle coupled to Fe(III) reduction. Our results show that AOM can substantially reduce methane emission from freshwater sediments, and the finding of AOM at sulfate concentrations −1 suggests that AOM could be of greater importance in freshwater systems, and in ancient low‐sulfate oceans, than was previously appreciated.

Anammox and denitrification in the oxygen minimum zone of the eastern South Pacific - Tage Dalsgaard; Bo Thamdrup; Laura Farías; Niels Peter Revsbech (Limnology and Oceanography, 2012)
We quantified the removal of fixed nitrogen as N 2 production by anammox and N 2 and N 2 O production by denitrification over a distance of 1900 km along the coasts of Chile and Peru, using short‐term incubations with 15 N‐labeled substrates. The eastern South Pacific contains an oxygen minimum zone (OMZ) characterized by an anoxic, nitrate‐ and nitrite‐rich layer of ∼ 200‐m thickness below 30–90 m of oxic water. Anammox and denitrification were almost exclusively recorded when the in situ O 2 concentration was below detection, indicating that the induction of these processes is highly oxygen sensitive. Anammox was detected in 70% of the samples from anoxic depths. Denitrification was detected in fewer samples, but maximum rates were an order of magnitude higher than those of anammox. In our incubations denitrification was responsible for 72% of the total N 2 production and 77% of the total removal of fixed nitrogen including N 2 O production. However, at the individual depths it could be one or the other process that was responsible for all of the nitrogen removal. Anammox activity was highest just below the oxic‐anoxic interface and declined exponentially with depth, whereas no depth dependence was discerned for denitrification. Denitrification resulted in net production of N 2 O in some of the samples and consumption of added 15 N 2 O in others. Together with the accumulation of this indicates that denitrification must be seen as a sequence of individually regulated reactions, each of which may start and stop depending on the electron donor input, while anammox is much less variable. The highly patchy distribution of denitrification contributes to explain the apparent imbalances between ammonium sources and sinks suggested by previous 15 N‐based studies in OMZs.

Nitrogen cycling in a deep ocean margin sediment (Sagami Bay, Japan) - Ronnie N. Glud; Bo Thamdrup; Henrik Stahl; Frank Wenzhoefer; Anni Glud; Hidetaka Nomaki; Kazumasa Oguri; Niels Peter Revsbech; Hiroshi Kitazato (Limnology and Oceanography, 2009)
On the basis of in situ NO 3 −1 microprofiles and chamber incubations complemented by laboratory‐based assessments of anammox and denitrification we evaluate the nitrogen turnover of an ocean margin sediment at 1450‐m water depth. In situ NO 3 −1 profiles horizontally separated by 12 mm reflected highly variable NO 3 −1 penetration depths, NO 3 −1 consumption rates, and nitrification. On average the turnover time of the pore‐water NO 3 −1 pool was ~0.2 d. Net release of NH 4 + during mineralization (0.95 mmol m −2 d −1 ) sustained a net efflux of ammonia (53%), nitrification (24%), and anammox activity (23%). The sediment had a relatively high in situ net influx of NO 3 −1 (1.44 mmol m −2 d −1 ) that balanced the N 2 production as assessed by onboard tracer experiments. N 2 production was attributed to prokaryotic denitrification (59%), anammox (37%), and foraminifera‐based denitrification (4%). Anammox thereby represented an important nutrient sink, but the N2 production was dominated by denitrification. Despite the fact that NO 3 −1 stored inside foraminifera represented ~80% of the total benthic NO 3 −1 pool, the slow intracellular NO 3 −1 turnover that, on average, sustained foraminifera metabolism for 12‐52 d, contributed only to a minor extent to the overall N 2 production. The microbial activity in the surface sediment is a net nutrient sink of ~1.1 mmol N m −2 d −1 , which aligns with many studies performed in coastal and shelf environments. Continental margin areas can act as significant N sinks and play an important role in regional N budgets.

Rates and regulation of anaerobic ammonium oxidation and denitrification in the Black Sea - Marlene M. Jensen; Marcel M. M. Kuypers; Lavik Gaute; Bo Thamdrup (Limnology and Oceanography, 2008)
We performed incubation experiments with 15 N‐labeled nitrogen compounds to investigate the vertical distribution of pathways of N 2 production through the suboxic zone of the central Black Sea and the impact of oxygen and sulfide on the anammox process. Anammox rates increased with depth through the upper suboxic zone and reached a maximum of ~11 nmol N 2 L −1 d −1 at the sharp interface between nitrate and ammonium, below which rates decreased toward the depth of sulfide accumulation. Heterotrophic denitrification was not detected, and therefore anammox was the prevailing sink for fixed nitrogen in the central Black Sea. In incubations with low oxygen concentrations, anammox activity was only partially inhibited, with a decrease in anammox rates to ~70% and 50% of the anoxic level at ~3.5 and ~8 µmol L −1 O 2 , respectively, and complete inhibition at ~13.5 µmol L −1 O 2 . Thus, the anammox process is not constrained to anoxic marine waters. This increases the volume of the major open‐ocean oxygen‐deficient zones, where anammox is potentially active, which has important implications for the contribution of anammox to the marine nitrogen cycle. We observed an inhibitory effect of micromolar sulfide concentrations on anammox activity, indicating that the vertical and likely horizontal distribution of active anammox bacteria is constrained to nonsulfidic water layers, which may explain the absence of the process in sulfidic basins with no suboxic zone.

Anaerobic ammonium‐oxidizing bacteria in marine environments: widespread occurrence but low diversity - Markus C. Schmid; Nils Risgaard‐Petersen; Jack Van De Vossenberg; Marcel M. M. Kuypers; Gaute Lavik; Jan Petersen; Stefan Hulth; Bo Thamdrup; Don Canfield; Tage Dalsgaard; Søren Rysgaard; Mikael K. Sejr; et al. (Environmental Microbiology, 2007)
Summary Laboratory and field studies have indicated that anaerobic ammonium oxidation (anammox) is an important process in the marine nitrogen cycle. In this study 11 additional anoxic marine sediment and water column samples were studied to substantiate this claim. In a combined approach using the molecular methods, polymerase chain reaction (PCR), qualitative and quantitative fluorescence in situ hybridization (FISH), as well as 15 N stable isotope activity measurements, it was shown that anammox bacteria were present and active in all samples investigated. The anammox activity measured in the sediment samples ranged from 0.08 fmol cell −1 day −1 N 2 in the Golfo Dulce (Pacific Ocean, Costa Rica) sediment to 0.98 fmol cell −1 day −1 N 2 in the Gullmarsfjorden (North Sea, Sweden) sediment. The percentage of anammox cell of the total population (stained with DAPI) as assessed by quantitative FISH was highest in the Barents Sea (9% ± 4%) and in most of the samples well over 2%. Fluorescence in situ hybridization and phylogenetic analysis of the PCR products derived from the marine samples indicated the exclusive presence of members of the Candidatus ‘Scalindua’ genus. This study showed the ubiquitous presence of anammox bacteria in anoxic marine ecosystems, supporting previous observations on the importance of anammox for N cycling in marine environments.

Anaerobic ammonium oxidation in a tropical freshwater system (Lake Tanganyika) - Carsten J. Schubert; Edith Durisch‐Kaiser; Bernhard Wehrli; Bo Thamdrup; Phyllis Lam; Marcel M. M. Kuypers (Environmental Microbiology, 2006)
Summary Here we provide the first direct evidence for the anammox process (anaerobic ammonium oxidation) in a lacustrine system, Lake Tanganyika, the second largest lake in the world. Incubations with 15 N labelled nitrate showed that anammox occurred in the suboxic water layer at 100–110 m water depth. Anammox rates up to 10 nM N 2 h −1 are comparable to those reported for the marine water column. Up to ∼13% of produced N 2 could be attributed to the anammox process whereas the remainder was related to denitrification. Typical lipid biomarkers characteristic of anammox bacteria were found in filtered water from the depths where anammox occurred, thus supporting the presence of anammox bacteria. Further evidence is provided by fluorescence in situ hybridization (FISH), revealing up to 13 000 anammox bacteria cells per ml or 1.4% of all DAPI (4′‐6‐Diamidino‐2‐phenylindole)‐stained cells. Phylogenetic analyses of partial 16S rRNA genes indicated the presence of sequences most closely related to the known anammox bacterium Candidatus ‘Scalindua brodae’ (95.7% similarity). Using the incubation results, a total loss of 0.2 Tg N 2 per year linked to anammox was estimated for the Northern basin of Lake Tanganyika.

Pathways of organic carbon oxidation in a deep lacustrine sediment, Lake Michigan - Uffe Thomsen; Bo Thamdrup; David A Stahl; Donald E. Canfield (Limnology and Oceanography, 2004)
Rates of microbial iron reduction and other pathways of organic carbon (Corg) oxidation were investigated in sediment from a 100‐m deep site in Lake Michigan. Total benthic mineralization rates of 6.8 and 8.0 mmol m −2 d −1 , respectively, were determined from benthic flux measurements and by summation of dissolved inorganic carbon (ΣCO 2 ) accumulation rates measured in anoxic incubations of sediment in discrete depth intervals to 18 cm depth. Carbon oxidation rates were highest near the sediment surface and decreased asymptotically toward zero. A C org half‐life of 0.06 yr was estimated in the oxic zone, but the half‐life increased by more than two orders of magnitude in the deep anoxic layers. Mineralization in the oxic zone (0‐2.1 cm) accounted for 37% of the total SCO2 production, whereas microbial iron reduction was the most important pathway of carbon oxidation, accounting for 44%; sulfate reduction accounted for 19%, and methanogenesis was negligible. Denitrification accounted for 2 d −1 .

High‐resolution metal gradients measured by in situ DGT/DET deployment in Black Sea sediments using an autonomous benthic lander - Gary R. Fones; William Davison; Ola Holby; Bo Barker Jorgensen; Bo Thamdrup (Limnology and Oceanography, 2001)
DET (Diffusive equilibration in thin films) and DGT (diffusive gradients in thin films) have been deployed in situ using an autonomous benthic lander to measure concentrations and induced fluxes of Fe and Mn (DET/DGT) and trace metals (DGT) in pore waters at millimeter spatial resolutions. The newly developed deployment system is described, and based on these first results, its strengths and weaknesses are discussed. Deployments were made in the Western Black Sea in shelf sediments overlain by well‐oxygenated water at a water depth of 77 m. Maxima of the redox‐sensitive metals at 4 and 8 cm deep within the sediment indicated that two zones of reduction dominated the geochemistry. Sharp, but systematic, features were superimposed on this general picture and were well replicated in the profiles of Mn, Co, and Cd, but the sharp features in the Fe profile were offset from those of the others elements by several millimeters. Detection of this functional discrimination between Fe and Mn as regulators of trace metals would not have been possible using more conventional sampling procedures.